MENINGKATKAN KETERAMPILAN PENGASUH ANAK BERKEBUTUHAN KHUSUS DALAM BIDANG BINA WICARA UNTUK ANAK TUNARUNGU-WICARA MELALUI PELATIHAN - Klemensia Nini; Maria Vianti Desa (Jurnal Pelayanan Pastoral, 2023)
The purpose of this study is to improve the skills of caregivers of children with special needs in the field of speech coaching in children with speech and language barriers due to speech deafness. The role of caregivers of children with special needs is to educate, coach, train and care so that they can grow and develop optimally. This research is a type of quantitative research and descriptive statistics as data analysis. The subjects of the study were caregivers of 11 children with special needs. The results of the pretest and posttest show that there is an increase in understanding and skills in the field of speech coaching in children who experience language and speech barriers. This is shown by the achievement of improvements in several indicators trained, namely 1) the concept of deaf-wicra-speech children by 36.4%, 2) understanding of various language and speech disorders by 29.5%, 3) understanding the concept of speech processes and the purpose of speech coaching by 36.4%, 4) understanding and skills for checking language and speech development, by 38.6% 5) understanding and skills in designing speech coaching programs by 38,6%.